2009
DOI: 10.1007/s11999-008-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Component Positioning in Hip Resurfacing With and Without Navigation

Abstract: Level III, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
6
31
0
5
Order By: Relevance
“…In a previous series retrospectively comparing 51 vs 88 consecutive HRs performed with and without navigation, respectively, using the same surgical approach, type of prosthesis and CAS system as used in this study, Ganapathi et al did not observe any inter-group differences in the mean native CCD angles, planned or post-operative SSAs. However, in accordance with the findings of our study, deviations between planned and post-operative SSAs of greater than five degrees were found in 33 patients (38 %) in the conventional group in contrast to none in the CAS group [17]. Taking this body of evidence from the current literature together with the results of our prospectively randomised study, we conclude that the use of CAS can prevent nonoptimal femoral component placement in HR.…”
Section: Systematic Review Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In a previous series retrospectively comparing 51 vs 88 consecutive HRs performed with and without navigation, respectively, using the same surgical approach, type of prosthesis and CAS system as used in this study, Ganapathi et al did not observe any inter-group differences in the mean native CCD angles, planned or post-operative SSAs. However, in accordance with the findings of our study, deviations between planned and post-operative SSAs of greater than five degrees were found in 33 patients (38 %) in the conventional group in contrast to none in the CAS group [17]. Taking this body of evidence from the current literature together with the results of our prospectively randomised study, we conclude that the use of CAS can prevent nonoptimal femoral component placement in HR.…”
Section: Systematic Review Resultssupporting
confidence: 91%
“…According to the literature an incidence of this end point of less than ten percent was assumed for the CAS implantation and of less than 40 % for the conventional method, respectively [17]. To detect the resulting clinically relevant incidence difference of 30 % in the primary end point by means of a two-sided Fisher's exact test at the five percent significance under minimum power of 80 %, the evaluation of 2×38 patients was found necessary.…”
Section: Study Design and Sample Size Justificationmentioning
confidence: 99%
“…However, other investigators have found no improvement in positioning [25,26]. It has also been shown that measurements provided by the navigation system are consistent with those obtained from postoperative radiographs [19,20,25] or CT images [27,28]. Our study did not show a significant difference in femoral component positioning between conventional and navigated implantation.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies have reported more accurate placement of the femoral component, mainly with respect to varus/valgus alignment, by using navigation in sawbones [18], cadavers [13][14][15][16]19] or patients [20][21][22][23][24]. However, other investigators have found no improvement in positioning [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Seyler, in a study comparing the accuracy of implantation of femoral components based on the experience of the surgeon, found an average accuracy compared to the planned angle SSA of 0.9-1.5°(p <0.17) [21]. Ganapathi et al found a difference of position with navigation less than 1°compared to planning in a retrospective study comparing 51 hips operated with navigation and 88 by the conventional technique [22]. These results are comparable to those of our technique and in some cases even better.…”
Section: Discussionmentioning
confidence: 99%